Effect of dietary tannin and protein concentration on resistance and resilience of chokla lambs against Haemonchus contortus - KHAN, FAIZ AHMAD; SAHOO, ARTABANDHU (The Indian Journal of Animal Sciences, 2023)
Feeding trial was conducted for 7 weeks using 5-6 months old chokla lambs reared in helminth free conditions. The source of condensed tannin was dried leaves of khejri (Prosopis cineraria). The animals were randomly allocated to six treatment groups: (1) Low protein (LP, 10.0% CP) throughout the trial, (2) high protein (HP, 18.4% CP) throughout the trial, (3) LP (for initial 3 weeks of the experiment) and then combination of LP and Khejri (K), (4) combination of LP and K throughout the trial, (5) HP (for initial 3 weeks of the experiment) and then combination of HP and K, and (6) combination of HP and K throughout the trial. At day 0, all groups were trickle infected with infective H. contortus larvae and subsequently with 400-500 larvae/animal three times per week for 6 weeks. Therewas no improvement in resilience as well as resistance of lambs fed with combination of LP concentrate and khejri leaves. Lambs (4-5) were given salvage treatment in each group. Bottle jaw condition was seen in two lambs in each group. There was similar reduction in both PCV and Hb parameters in all the three groups fed with LP concentrate without any influence of inclusion of khejri leaves in the diet. Similarly CT inclusion did not influence the faecal egg count (FEC). On the other hand, improvement in both resistance and resilience was observed in lambs fed with combination of HP concentrate and khejri leaves. Inclusion of khejri leaves in HP concentrate fed lambs significantly affected both PCV and Hb. Faecal egg count was also significantly affected. There was significant effect on average daily gains (ADG). Voluntary feed intake was obtained in collective pens. Although there was reduction in feed intake in all the groups during week 2 to 3, it was more evident in lambs kept on LP concentrate. Therefore, it was suggested that when tannin was included with HP concentrate, an additive effect was seen which resulted in increase in protein availability to the lambs.